Integrated ecosystem research in the Pacific Arctic – understanding ecosystem processes, timing and change. (July 2020) - Baker, Matthew R.; Farley, Edward V.; Ladd, Carol; Danielson, Seth L.; Stafford, Kathleen M.; Huntington, Henry P.; Dickson, Danielle M.S.
Abstract: Arctic marine ecosystems are experiencing substantial changes associated with sea ice loss and surface warming. The most obvious and dramatic changes include earlier ice retreat and a longer ice-free season, particularly on Arctic inflow shelves, including the Barents Sea in the Atlantic Arctic and the northern Bering Sea and Chukchi Sea in the Pacific Arctic. The extreme variability observed in recent years in the Pacific Arctic is unparalleled in recorded history. This volume is devoted to studies that integrate research across various components of the Arctic marine ecosystem to better characterize these changes. The intent of this integrated approach is to better understand the linkages and interactions that shape ecosystem processes, influence timing and phenology of events, and inform predictions of future conditions. The studies presented in this Special Issue investigate processes in the Bering Sea, Chukchi Sea, and Beaufort Sea. The data derive from remote sensing, ship-based surveys, and integrated data products. The research presented includes time-series analyses on environmental change across the greater Pacific Arctic, heat flux, stratification and mixing dynamics, vertical structure, and wind and current patterns. It explores the influence of physical processes on, and seasonal and annual variability in, primary production, nutrient distribution, and the export of biogenic matter. It also examines the effects of oceanographic variability on zooplankton taxa, the distribution of larval fishes, age and growth in Arctic fishes, responses of salmon to warming, and variability in cetacean occurrence. These studies are designed to provide new insights on integrated ecosystem research in the Pacific Arctic, with a focus on improving understanding of ecosystem processes, timing and change. This volume marks the first in a series of research volumes supported by the North Pacific Research Board to integrate ecosystem research in the Pacific Arctic and to inform our collective understanding of the rapid transformation in this region.